SARS-CoV-2 mRNA Vaccine Attitudes as Expressed in U.S. FDA Public Commentary: Need for a Public-Private Partnership in a Learning Immunization System - Weitzman, Elissa R.; Sherman, Amy C.; Levy, Ofer (Frontiers in Public Health, 2021)
As part of the U.S. Food and Drug Administration COVID-19 vaccine review process, public commentary was solicited offering an opportunity to reflect on vaccine attitudes that may impact the uptake of coronavirus vaccines. We identified themes in the commentary that highlighted the safety, efficacy, ethics, and trustworthiness and transparency regarding the novel mRNA COVID-19 vaccines. A “Learning Immunization System” model is proposed to optimize public, private, and academic partnerships relating to vaccine development and implementation.